Effects of hematite-lead oxide combination in ethylene-propylene-diene-monomer on shielding 59.54 keV gamma rays - Kamat V.A; George B; Kiran K.U; Somashekarappa H.M; Swaroop K (Radiation Physics and Energy, 2019)
Ethylene-propylene-diene-monomer (EPDM) was filled with metal oxides like PbO and Fe2O3 and analysed for peroxide vulcanization kinetics, radiation shielding ability, and thermal stability. Increase in crosslinking density was observed with Fe2O3 concentration in the lead oxide-hematite-EPDM (LHE) composites, and radiation shielding property upon addition of total 60 phr fillers was discussed. Among the synthesised composites, P60F0 and P40F20 showed good shielding ability for 59.54 keV gamma rays. All the composites showed good electrical insulation up to 50kHz AC frequency. Moreover, the P40F20 composite contained relatively less lead content than the )60F0 composite, and also, the mechanical strength and thermal stability of P40F20 was greater than that of the P60F0 composite and therefore, it can be considered as a good shielding material
Keywords: Activation energy; Attenuation coefficient; Polymer composites; RAdiation shielding